Continuous versus intermittent electrical stimulation of beef carcasses and their effect on hot-boned Muscle-pH decline - Bowles, J.E.; Hunt, Melvin C.; Kendall, J.L.A.; Lyon, M.; Kastner, Curtis L.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
Short bursts of electricity (intermittent electrical stimulation) to beef carcasses accelerated pH decline and the onset of rigor mortis more than continuous stimulation did.
Keywords: Beef; Electrical stimulation; pH; Hot-boned